Textbook of Real-Time Three Dimensional Echocardiography - Badano, Luigi; Lang, Roberto M.; Zamorano, Jose Luis.; SpringerLink (Online service) (London : Springer London, 2011)
Tremendous improvements in ultrasound technology have led to development of one of the most impressive advancements in the use of ultrasound to assess cardiac morphology and function: three-dimensional echocardiography (3DE). During the last decade, 3DE has made a dramatic transition from a predominantly research tool used in few large academic medical centers to a technology available in most echocardiography laboratories, cardiac surgery operating rooms and catheterization and/or electrophysiology labs to address everyday clinical practice and guide interventional procedures. 3DE is now an established technique able to provide intuitive recognition of cardiac structures from any spatial point of view and complete information about absolute heart chamber volumes and function. In particular, 3DE has demonstrated its superiority over current echocardiographic modalities in a number of clinical applications. The Textbook of Real-Time Three Dimensional Echocardiography is intended to provide a comprehensive overview of the normal anatomy of the heart as seen by this new revolutionary ultrasound technique, and focusing on the clinical value of transthoracic 3DE and on the expanding role of transesophageal 3DE in guiding and monitoring surgical and interventional procedures. For echocardiographers who already use 3DE, the more advanced applications of 3DE are presented in detail. For those looking to learn 3DE, the Editors and their contributors have provided hundreds of images and videos in an that show the added clinical value of 3D imaging of cardiac structures. This textbook is therefore written not only for cardiologists specifically involved in the imaging of patients but also for general cardiologists, since it offers a wider clinical view of normal and pathological cardiac anatomy.
1. The evolution of three dimensional echocardiography -- Extrinsic tracking: positional and freehand acquisition -- Gated sequential imaging -- Integrated transesophageal approach and rotational transducer -- Real-time imaging -- 2. Principles of transthoracic three-dimensional acquisition and image display -- Matrix transducer design and technology -- Beam forming in three spatial dimensions -- Data processing -- Image resolution and display -- Image artifacts -- Three-dimensional color Doppler display and quantification -- Measuring in three dimensions -- Future developments -- 3. Principles of transesophageal three-dimensional acquisition and image display -- Matrix transducer design and technology -- Beam forming in three spatial dimensions -- Data processing -- Image resolution and display -- Image artifacts -- Unique quantification opportunities by transesophageal approach -- Future developments -- 4. Three-dimensional echocardiography in clinical practice -- Advantages over the two-dimensional modality -- Orientation of the heart and imaging views -- Acquisition modes and image display -- Implementing 3D echo in routine clinical practice -- 5. Three-dimensional echocardiographic evaluation of the left ventricle -- Validation studies -- Assessment of volume, shape and function -- Assessment of regional wall motion -- Assessment of mass -- Contrast enhancement -- Future directions -- 6. Advanced evaluation of left ventricular function with three dimensional echocardiography -- Assessment of intraventricular dyssynchrony -- Stress echocardiography -- Assessment of myocardial deformation -- Assessment of myocardial perfusion -- Future directions -- 7. Three-dimensional echocardiographic evaluation of the mitral valve -- Three dimensional echocardiographic anatomy of the normal mitral valve -- Mitral valve regurgitation -- Organic mitral valve regurgitation -- Functional mitral valve regurgitation -- Assessment of the degree of regurgitation -- Mitral valve stenosis -- Morphological assessment -- Functional assessment -- Monitoring percutaneous mitral valvuloplasty -- Mitral valve endocarditis -- 8.Three-dimensional echocardiographic evaluation of the aortic valve and the left ventricular outflow tract -- Three dimensional echocardiographic anatomy of the normal aortic valve -- The bicuspid aortic valve -- Assessment of aortic valve stenosis -- Assessment of aortic valve regurgitation -- Aortic valve endocarditis -- 9. Three dimensional echocardiographic evaluation of the right heart chambers -- The right ventricle -- Anatomy and function -- The tricuspid valve -- Normal anatomy -- Tricuspid regurgitation -- Tricuspid stenosis -- Tricuspid valve endocarditis -- The pulmonary valve -- Normal anatomy -- Pulmonary valve disease -- Pulmonary valve endocarditis -- 10. Three dimensional echocardiography in congenital heart disease -- 11. Three dimensional echocardiography to assess intracardiac masses -- Thrombi -- Benign Cardiac Tumors -- Malignant Cardiac Tumors -- Metastatic Tumors -- Devices -- 12. Use of three-dimensional echocardiography to guide intracardiac procedures -- 13. Future developments of three-dimensional echocardiography -- 14. Real-time three-dimensional transesophageal echocardiography -- 15. Real-time three dimensional echocardiography in mitral valve repair procedures -- 16. Visualization and assessment of coronary arteries with real-time three dimensional echocardiography -- 17. Three-dimensional echocardiography to assess cardiac geometry and function in athletes -- 18 Role of three-dimensional echo in drug trials -- Heart Failure -- Hypertension.
Keywords: Medicine; Radiology, Medical; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Imaging / Radiology; Internal Medicine